1998
DOI: 10.1121/1.423932
|View full text |Cite
|
Sign up to set email alerts
|

Nonmonotonicity of informational masking

Abstract: Neff and Green [Percept. Psychophys. 41, 409-415 (1987)] report that the masking of single tones by random-frequency multitone maskers varies nonmonotonically with number of masker components (peaking at 10-50 components). In this paper it is shown that such results are well predicted by a model (the component-relative-entropy model, CoRE) wherein thresholds increase linearly with the ensemble variance of masker spectra smoothed by peripheral auditory filters [R. A. Lutfi, J. Acoust. Soc. Am. 94, 748-758 (1993… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
107
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(113 citation statements)
references
References 25 publications
6
107
0
Order By: Relevance
“…They proposed that this result could be explained by the fact that the subjects with hearing loss needed to listen at such high signal-to-noise ratios that the masker and target speech were easy to differentiate (i.e., simply listening for the louder target message reduced informational masking). Alternatively, Arbogast, et al also suggested that there may be an inverse relationship between the amount of energetic masking and the amount of informational masking, as has been shown in tonal informational masking tasks (e.g., Kidd, Mason, Brughera, & Chiu, 2003;Neff & Green, 1987;Oh & Lutfi, 1998). The results of Hornsby, Ricketts, and Johnson (2006) indicated that normal-hearing and hearing-impaired listeners yield similar amounts of increased masking when performance with a speech masker is compared to that obtained with speech-modulated noise.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…They proposed that this result could be explained by the fact that the subjects with hearing loss needed to listen at such high signal-to-noise ratios that the masker and target speech were easy to differentiate (i.e., simply listening for the louder target message reduced informational masking). Alternatively, Arbogast, et al also suggested that there may be an inverse relationship between the amount of energetic masking and the amount of informational masking, as has been shown in tonal informational masking tasks (e.g., Kidd, Mason, Brughera, & Chiu, 2003;Neff & Green, 1987;Oh & Lutfi, 1998). The results of Hornsby, Ricketts, and Johnson (2006) indicated that normal-hearing and hearing-impaired listeners yield similar amounts of increased masking when performance with a speech masker is compared to that obtained with speech-modulated noise.…”
mentioning
confidence: 93%
“…Arbogast, et al (2005) found less informational masking in a group of listeners with hearing loss varying in age from 21 years to 79 years, as compared to age-matched normal-hearing participants. They proposed that this result could be explained by the fact that the subjects with hearing loss needed to listen at such high signal-to-noise ratios that the masker and target speech were easy to differentiate (i.e., simply listening for the louder target message reduced informational masking Mason, Brughera, & Chiu, 2003;Neff & Green, 1987;Oh & Lutfi, 1998). The results of Hornsby, Ricketts, and Johnson (2006) indicated that normal-hearing and hearing-impaired listeners yield similar amounts of increased masking when performance with a speech masker is compared to that obtained with speech-modulated noise.…”
mentioning
confidence: 99%
“…The elevations in threshold can be quite large. When masker uncertainty is introduced by varying the frequencies and levels of masker components at random on each presentation, the amount of informational masking of a puretone signal can be as much as 50 dB for well-trained adult listeners (Neff & Callaghan, 1987, 1988Neff & Green, 1987;Oh & Lutfi, 1998). For preschool-age children performing in very similar conditions it can be in excess of 70 dB (Oh, Wightman, & Lutfi, 2001).…”
mentioning
confidence: 99%
“…Like many modern studies of masking (e.g., Kidd, Mason, Deliwala, Woods, & Colburn, 1994;Neff & Dethlefs, 1995;Oh & Lutfi, 1998), Experiment 1 used an adaptive procedure to directly estimate thresholds corresponding to p .69. Adaptive procedures efficiently provide direct estimates of thresholds and, thus, the magnitude of masking in physical terms that are easily understood.…”
Section: Methodsmentioning
confidence: 99%